THE IMPORTANCE OF SCREENING IN HUMAN HEALTH: EARLY DETECTION AND PREVENTIVE IMPACT (Modern education and development, 2025)
Screening is a vital public health strategy used to identify diseases in their early stages, often before symptoms appear. This paper explores the significance of screening in maintaining human health, with a focus on its role in early detection, disease prevention, and reducing healthcare costs. Emphasis is placed on commonly screened conditions such as cancer, cardiovascular diseases, and metabolic disorders.